Gen Y Green Purchasing Behavior in Relation to Energy Conservation and Environmental Preservation Products in Malaysia - Rajadurai, Jegatheesan; Bathmanathan, Vathana; Azami, Nurnazurah (International Journal of Engineering and Technology, 2018)
The significant increase in the effect of global warming has given more attention to consumers to protect and preserve the environment.Â This is evident as we see the purchasing trends of consumers moving towards environmentally friendly products. In Malaysia consumers consist of three main generations with varied purchasing behaviors. The aim of this study is to investigate the variables affecting Gen Y consumerâ€™s green purchasing behavior. Phase 1 being qualitative in nature, involved five focus group interview sessions and a pilot study, while phase 2, being quantitative, involved the distribution and collection of questionnaires to Gen Y consumers of green products. The independent variables that affect green purchasing behavior are environmental concerns, attitudes towards the environment and environmental knowledge. Awareness of environmental problems was found not to be the variable that affects Gen Y green purchasing behavior. The implications of this study are that it supports energy conservation and environmental preservation businesses to better understand the green market environment, its opportunities and potential, enables businesses to better market their products, create products with competitive advantages and encourage the consumerâ€™s green purchasing intentions. Subsequently, this study assists the government or policy makers to promote green purchasing behavior among the Malaysia population.